Innovative therapies for acute bacterial skin and skin-structure infections (ABSSSI) caused by methicillin-resistant Staphylococcus aureus: advances in phase I and II trials. (3rd May 2020) - Bassetti, Matteo; Del Puente, Filippo; Magnasco, Laura; Giacobbe, Daniele Roberto
ABSTRACT: Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) is among the most frequent causative agents of acute bacterial skin and skin-structure infections (ABSSSI) and has been associated with increased risks of invasive disease and of treatment failure. Areas covered: In this review, we focus on those novel anti-MRSA agents currently in phase I or II of clinical development that may enrich the armamentarium against ABSSSI caused by MRSA in the future. Expert opinion: Promising agents belonging to either old or novel antibiotic classes are currently in early phases of clinical development and may become available in the future for the effective treatment of ABSSSI caused by MRSA. In particular, the future availability of agents belonging to novel classes will be important for guaranteeing an effective treatment and for allowing outpatient treatment/early discharge, with a consequent reduced impact on healthcare resources. However, this does not mean that we can relax our efforts directed toward improving the responsible use of already available agents. Indeed, preserving their activity in the long term is crucial for optimizing the use of healthcare resources.